Fibrin clot characteristics in acute ischaemic stroke patients treated with thrombolysis: the impact on clinical outcome - Bembenek, Jan P.; Niewada, Maciej; Siudut, Jakub; Plens, Krzysztof; Członkowska, Anna; Undas, Anetta (Thrombosis and Haemostasis, 2017)
Fibrin clot properties in acute ischaemic stroke (AIS) are unfavourably altered, including faster formation of denser and poorly lysable fibre networks. We investigated clot properties in AIS patients treated with recombinant tissue plasminogen activator (rtPA) and their impact on clinical outcome. In 74 consecutive AIS patients eligible for rtPA treatment, we assessed ex vivo plasma fibrin clot formation, permeability (Ks), and rtPA-induced lysis, along with peak thrombin generation, fibrinolysis proteins and inhibitors at three time points – on admission, after 24 hours and 3 months since stroke. Clinical outcome was assessed using the NIHSS and mRS scores. Compared with the pretreatment values, fibrin networks assessed 24 hours since thrombolysis were formed more slowly (+20.5 % lag phase on turbidimetry), were less compact (+36.9 % Ks), composed of thinner fibres (-10.6 % lower maximum absorbancy [ΔAb]), which were lysed more rapidly (-20.8 % clot lysis time [CLT] and +7.1 % the rate of rtPA-induced D-dimer release from clots [D-Drate]). Thrombin generation and fibrinolysis proteins remained elevated. Lower ΔAb (<0.86 at 405 nm), shorter CLT (<105 min), and higher D-Drate (>0.072 mg/l/min) assessed at baseline predicted good outcome (mRS 0–2) at 3 months after adjustment for age and fibrinogen. Logistic regression adjusted for potential confounders showed that good outcome at 3 months was predicted by pretreatment D-Drate, while pretreatment CLT predicted excellent outcome (mRS of 0–1). In conclusion, formation of denser fibrin clots displaying impaired lysability and pattern of their changes induced by thrombolysis may affect clinical outcome in AIS patients.
Keywords: Stroke; thrombolysis; thrombosis; tissue plasminogen activator; treatment outcome